QUASI-MONTE CARLO METHODS BASED ON SOBOL AND HALTON SEQUENCES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS APPLIED IN SECURITY SYSTEMS: QUASI-MONTE CARLO METHODS BASED ON SOBOL AND HALTON SEQUENCES FOR COMPUTATION OF MULTIDIMENSIONAL INTEGRALS APPLIED IN SECURITY SYSTEMS - Todorov, Venelin; Tsvetkov, Iliyan; Stanchev, Tosho; Dimitrov, Yuri (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper we implement and analyze the performance of Sobol quasi-random sequence and compare the results with the Halton quasi-random sequence has been done. We consider a case study with a non-smooth integrand function with applications in financial mathematics. We show that the Sobol sequence has some advantageous over the Halton sequence. It is established that Sobol sequence performs bett er than other sequences for higher dimensions.